EFEKTIVITAS PENGKOMPOSAN SAMPAH KOTA DENGAN MENGGUNAKAN Ã¢â‚¬Å“KOMPOSTERÃ¢â‚¬Â SKALA RUMAH TANGGA - Sahwan, Firman Laili (Jurnal Teknologi Lingkungan, 2004)
Composting as one of efforts to overcome municipal solid waste problem has enough potency because 70-80 % of municipal solid waste is organic material, mostly can be processed to compost. Composting in source of waste (household) will be more effective because is easier (small scale) and cheaps (transport is not necessary). Composting can be done by using composter. Research result showing that composter is easy to be made, easy to be applied in our society and effective enough to use in producing municipal waste compost. The compost processing time is 49 days and producing the good quality of compost.